STUDY OF THE INFLUENCE OF FLAT KNITTING EQUIPMENT TYPE ON THE BREAKING LOAD AND ELONGATION OF KNITTED FABRIC MADE FROM HIGH-STRENGTH THREADS - ДМИТРИК, О. М.; ГАЛАВСЬКА, Л. Є. (Technologies and Engineering, 2024)
Purpose. Study of the effect of changing of flat knitting equipment type (with or without sinkers) affects the strength characteristics of the knitted material of the plain interloping, made of high molecular weight polyethylene and para-aramid threads. Methodology. The work is based on the theory of knitting, methods of analysis and synthesis of the obtained results, the use of the basics of textile material science. The resistance characteristics of the developed knitted material samples were determined using the KT-7010AZ electronic tearing machine and in accordance with standardized methodology. In order to identify the effect of knitting density on the amount of tensile load and elongation of the studied samples of knitted materials, the method of linear regression analysis was implemented in the traditional planning of an active experiment. The Microsoft Excel program was used to process the results of the experiment and draw graphs based on the average values of the indicators. The results. In the course of the research, it was found that the type of flat knitting equipment affects the breaking characteristics of knitted material made from high molecular weight polyethylene and para-aramid threads, namely: the presence or absence of sinkers when forming loops. The participation of sinkers in the process of looping determines the formation of a given length of the thread in the area of the sinker of the loops. This, in turn, affects the tensile elongation of the knitted material. Samples of knitted material from high molecular weight polyethylene threads showed better results in terms of resistance to the applied breaking force both in the direction of course and in the direction of wales. The value of the specific elongation at break per wale or course, in the case of producing knitted material on flat-knitting equipment without sinkers with a general takedown force of the fabric, a change in knitting density has a slight effect (up to 5%). Scientific novelty. The nature of the influence of flat-knitting equipment type (with and without sinkers) on the strength characteristics of the knitted material of the plain interloping, made from high-molecular polyethylene and para-aramid threads, has been established. Practical significance. The regression dependencies obtained during the experiment make it possible to determine the value of the breaking load and elongation of thee knitted material of the plain interloping, made from high molecular weight polyethylene and para-aramid threads, in accordance with the selected type of flat knitting equipment and the knockover depth value.